PENGARUH MODEL TIGA FAKTOR FAMA DAN FRENCH TERHADAP EXPECTED RETURN: STUDI PADA TUJUH SAHAM PERBANKAN KONVENSIONAL DI INDONESIA - Alfi Muflikhah Lestari (Universitas Negeri Medan, 2015)
This research aims to look at the influence of three factors model of Fama and Frencagainst the expected return on a stock of conventional bankaing with seven best performance in Indonesia the period 2010-2014. The data used are secondary data with quantitative research approach by using a classic assumption test. The research result showed that (1) Return the market has a positive influence but not significantly to your expected return, (2) Size SMB has a positive and significant influence against the expected return and (3) Book to market value (HML) has a positive and significant influence against expected return.